Children's Songs in Nawfija Community, Southeastern Nigeria: A sociolinguistic perspective - Okeke, Chinazam (School of African and GenderStuds, Anth and Ling, 2024)
This thesis studies the Indigenous children's songs of the Nawfija community, in the Southeastern part of Nigeria. The language of communication in the community is the Nawfija variety of Igbo. The research was conducted from a sociolinguistic perspective, shaped by the participants' ideas and perceptions, thereby allowing their voices to be heard. Adopting a qualitative paradigm, the study employed interviews and observations for data collection. 20 participants were interviewed, and observations were carried out in five households. The study draws on language socialization and language ideologies as its theoretical frameworks. The study shows, firstly, that Indigenous songs serve as an important language socialization tool in the Nawfija community. Secondly, it shows that the songs have declined in their use over time. The decline can be linked to the histories of colonialism, a western education model, globalization, and religion. At the same time, new practices have emerged. For example, cell phones, toys, DVDs, and CDs are now often used in child care. In addition, localized English songs, afro-beats, reggae, and hip-hop, are used when looking after children. The research discusses three ideologies surrounding these Indigenous songs, two of which, (i) and (ii), may have contributed to their decline. The ideologies are (i) English equates to intelligence and success, (ii) English is the language of geographical mobility, and (iii) Igbo/Nawfija variety is a language of identity. The study concludes by arguing that, as a result of ideologies (i) and (ii), if these Indigenous children's songs were revitalized, possibly, not all community members would be committed to maintaining them. Therefore, for the revitalization to be successful, people need to appreciate the importance, beauty, and value of their languages and cultural practices (see ideology (iii)). Likewise, the Nigerian academic system should be shaped to reflect their uniqueness and promote their language and its practices, by adopting the local variety as the primary language of education. This will help to strengthen people's knowledge of their history, language, linguistic practices, culture, knowledge, present realities, and future challenges.